Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18632/oncotarget.14852
|View full text |Cite
|
Sign up to set email alerts
|

Association of plasma ghrelin levels and ghrelin rs4684677 polymorphism with mild cognitive impairment in type 2 diabetic patients

Abstract: Background and aimsPeople with insulin resistance and type 2 diabetes mellitus (T2DM) are at increased risks of cognitive impairment. We aimed to investigate the association of plasma ghrelin levels and ghrelin rs4684677 polymorphism with mild cognitive impairment (MCI) in T2DM patients.ResultsIn addition to elevated glycosylated hemoglobin (HbA1c), fasting blood glucose (FBG) and homeostasis model assessment of insulin resistance (HOMA-IR), T2DM patients with MCI had decreased plasma ghrelin levels compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 44 publications
0
9
0
Order By: Relevance
“…In our previous study, we found higher HbA1c level, in T2DM patients with MCI than these without MCI. 51 , 52 These factors may limit the accuracy of results as confounding factors for a cross-section study. So, in the later analysis, these factors were corrected.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we found higher HbA1c level, in T2DM patients with MCI than these without MCI. 51 , 52 These factors may limit the accuracy of results as confounding factors for a cross-section study. So, in the later analysis, these factors were corrected.…”
Section: Discussionmentioning
confidence: 99%
“…The protein encoded by the ghrelin gene is the ligand for the growth hormone secretagogue receptor, which mainly regulates the concentration of growth hormone in the body and affects some of the body’s functions through affecting the release of growth hormone, such as regulating growth and development, affecting sugar, lipid and protein metabolism, and relaxing the cardiovascular system [ 16 , 17 ]. It has been proved that the ghrelin gene polymorphisms can affect the occurrence and susceptibility to a variety of diseases, such as polycystic ovary syndrome [ 18 ], chronic hepatitis C [ 19 ], and type 2 diabetes mellitus [ 20 ]. In cerebral infarction patients, the effects of ghrelin gene polymorphisms have not been studied yet.…”
Section: Discussionmentioning
confidence: 99%
“…Ghrelin was also involved in the neuro-modulation, neuro-protection and memory and learning processes [110]. Reduced ghrelin levels were associated with MCI in type 2 diabetes (T2DM) populations [111] and with metabolic changes in AD patients [112]. However, a recent study found that ghrelin modulated encoding-related brain function without enhancing memory formation in humans [113].…”
Section: Energy Homeostasis Dysfunctionmentioning
confidence: 99%